The role of sex in the association between cannabis use and working memory‐related brain activity. Issue 6 (15th March 2022) - Kroon, Emese; Kuhns, Lauren N.; Kaag, Anne Marije; Filbey, Francesca; Cousijn, Janna
Abstract: Although cannabis use patterns differ between men and women, studies on sex differences on the effects of cannabis on the brain and cognitive control are largely lacking. Working memory (WM) is a component of cognitive control believed to be involved in the development and maintenance of addiction. In this study, we evaluated the association between cannabis use and WM (load) related brain activity in a large sample, enabling us to assess sex effects in this association. The brain activity of 104 frequent cannabis users (63% men) and 85 controls (53% men) was recorded during an N‐back WM task. Behavioral results showed a significant interaction between WM load and group for both accuracy and reaction time, with cannabis users showing a relatively larger decrease in performance with increasing WM load. Cannabis users compared to controls showed a relatively smaller reduction in WM (load) related activity in the precuneus and posterior cingulate cortex at higher WM load. This WM (load) related activity was not associated with performance nor cannabis use and related problems. An exploratory analysis showed higher WM‐related activity in the superior frontal gyrus in men compared to women. While cannabis users showed higher WM (load) related activity in central nodes of the default mode network, this was not directly attributable to group specific worsening of performance under higher cognitive load. Further research is necessary to assess whether observed group differences increase with higher cognitive load, how group differences relate to measures of cannabis use, and how sex affects these group differences. Abstract : Compared to controls, cannabis users show a relatively larger decrease in performance with increasing working memory (WM) load and a relatively smaller reduction in WM related activity in the precuneus and posterior cingulate cortex at higher WM load. No sex differences emerged generally or in cannabis users in WM and WM load related activity or performance.